FETAL GROWTH RESTRICTION IN PORPHYROMONAS GINGIVALIS-INFECTED PREGNANT RATS: RESTRI KSI PERTUMBUHAN JANIN PADA TIKUS HAMIL YANG DIINFEKSI PORPHYROMONAS GINGIVALIS (Dentika: Dental Journal, 2011)
The periodontopathogens Porphyromonas gingivalis may directly or indirectly attack the fetus by releasing toxins into the blood stream that could reach the placental and influence fetal development . This study aimed to determine the effect of periodontal infection with P. gingivalis on fetal development in pregnant rat model. Female rats were infected with live-P. gingivalis at concentration of 109colony forming unit/ml into subgingival sulcus before and/or during pregnancy. Group I: without P. gingivalis infection ; group II: P. gingivalis infection before and during pregnancy; group III: P. gingivalisinfection before pregnancy; and group IV: P. gingivalis infection during pregnancy. They were sacrified on gestational day 14 and 20. Fetuses were evaluated for weight and crown-tail length. The results showed that the dams infected with P.gingivalis significantly decrease the mean of fetal weights, lengths and placental weights compared with the control group (p